2019
DOI: 10.1093/jhps/hnz056
|View full text |Cite
|
Sign up to set email alerts
|

Indications for hip arthroscopy in pediatric patients a systematic review

Abstract: The purpose of this study was to evaluate the current available literature on hip arthroscopy and determine the clinical indications in the pediatric patient population (age ≤ 18). In accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), a comprehensive literature search was performed on the 23 October 2018 using PubMed, Cochrane Library, Embase and e-books to identify research surrounding the use of hip arthroscopy in the pediatrics. Exclusion criteria were studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Hip arthroscopy in the pediatric population is known to be a particularly challenging procedure, mainly due to anatomical variation in the skeletally immature patient. 2,8,37 A significant decrease in the neck-shaft angle and anteversion must be kept in mind when positioning the patient and care must be taken to respect the open physes. Additionally, due to the immaturity of the acetabulum, theoretical risks of slipped capital femoral epiphysis (SCFE), avascular necrosis, and infection do exist.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroscopy in the pediatric population is known to be a particularly challenging procedure, mainly due to anatomical variation in the skeletally immature patient. 2,8,37 A significant decrease in the neck-shaft angle and anteversion must be kept in mind when positioning the patient and care must be taken to respect the open physes. Additionally, due to the immaturity of the acetabulum, theoretical risks of slipped capital femoral epiphysis (SCFE), avascular necrosis, and infection do exist.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of scientific evidence regarding the role of arthroscopy in LCPD. Several studies have shown that arthroscopy improves function in LCPD patients and has multiple advantages over open hip surgery including smaller incisions, a shorter recovery period, reduced damage to already damaged articular cartilage, and reduced risk of avascular necrosis of femoral head 3 4) . There is no synthesis of information in the form of a systematic review on indications and outcomes of hip arthroscopy in sequelae of LCPD, therefore the aim of the current study is to evaluate existing literature regarding the role and outcomes of hip arthroscopy in LCPD.…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic labral repair and osteochondroplasty are options for correcting intra-articular abnormalities [ 5 ]. Indications for arthroscopy for LCPD include recalcitrant hip pain, intra-articular pathology including loose bodies, labral tears and cartilage lesions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%